Dental management of lymphangiomatosis: case report. (8th May 2019) - Charrette, D.; Mulvihill, C.; Brady, P.
Abstract: Lymphangiomatosis is a rare type of diffuse tumour, which develops from an aberrant growth of the lymphatic vessels, and can produce progressive osteolysis of bone in multiple organ systems. In this article, we illustrate a rare case of a 14‐year‐old female patient with lymphangiomatosis affecting the maxillofacial bones. The patient showed a marked deviation from normal maxillofacial growth patterns resulting in significant malocclusion and oral complications. The present study examines and considers the multidisciplinary management of the case with a brief review of the literature.